2017
DOI: 10.1002/term.2316
|View full text |Cite
|
Sign up to set email alerts
|

Corneal keratocyte transition to mesenchymal stem cell phenotype and reversal using serum-free medium supplemented with fibroblast growth factor-2, transforming growth factor-β3 and retinoic acid

Abstract: . (2016) Corneal keratocyte transition to mesenchymal stem cell phenotype and reversal using serum-free medium supplemented with FGF-2, TGF-ß3 and retinoic acid. Journal of Tissue Engineering and Regenerative Medicine . ISSN 1932-7005 Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/39574/1/Author%27s%20manuscript.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 50 publications
(69 reference statements)
3
24
0
1
Order By: Relevance
“…Experiments on 2D controls of the same formulations demonstrated that chemistry was the dominant effect on cell adhesion in these studies (rather than fiber morphology). ALDH3A1 and CD34 are important markers of keratocytes in vivo alongside keratocan expression . The expression of CD90 (gene name THY1 ) and α‐SMA (gene name ACTA2 ) are characteristic of a less desirable myofibroblastic phenotype that leads to scarring .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Experiments on 2D controls of the same formulations demonstrated that chemistry was the dominant effect on cell adhesion in these studies (rather than fiber morphology). ALDH3A1 and CD34 are important markers of keratocytes in vivo alongside keratocan expression . The expression of CD90 (gene name THY1 ) and α‐SMA (gene name ACTA2 ) are characteristic of a less desirable myofibroblastic phenotype that leads to scarring .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work published by our laboratories have compared similar isolated cells cultured in vitro to those resident in the native cornea. Compared to the native cornea, ALDH3A1, CD34, and ACTA2 were significantly downregulated and THY1 was significantly upregulated . This suggests that when cultured in vitro , the whole population of cells do not differentiate to the keratocyte phenotype warranting further optimization of scaffold morphology and in vitro culture conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations